can you solve this question for me

Question # 40428
  • Math
    7 months ago
    $ free
    7 months ago

    A245


    Question 

    If the graph of y = f(x) is transformed into the graph of 2y - 6 = - 4 f(x - 3), point (a , b) on the graph of y = f(x) becomes point (A , B) on the graph of 2y - 6 = - 4 f(x - 3) where A and B are given by
    A. A = a - 3, B = b
    B. A = a - 3, B = b
    C. A = a + 3, B = -2 b
    D. A = a + 3, B = -2 b +3

    Answers Received (2)

    DrJanet

    (6 reviews)

    Best Answer

    Tutor Earned: $0.04 7 months ago

    profgera

    (1 reviews)

    7 months ago